RECYCLING OF HIGH QUALITY STEEL SCRAPS DIRECTLY IN ELECTROSLAG REMELTING PROCESS (ESR) - Birol, Burak; Saridede, Muhlis Nezihi (JOHN WILEY & SONS, 2011)
The scraps of high quality steels generally contain expensive alloying elements such as chromium, vanadium, nickel, etc. These scraps are melted in an induction or an electric arc furnace and refined in ESR (Electroslag Remelting) purification process. A significant amount of alloying elements are lost during these processes. In order to avoid these losses, scraps can be utilized directly in ESR by skipping the melting step. In this study, 316L stainless steel scraps were refined in ESR with selected synthetic slags. The products were analyzed by optic emission spectrometry and the effects of slag compositions on the alloying element losses were examined. According to the analysis of the scrap and the products, generally chromium, nickel and manganese losses were encountered. It was determined that the alloying element losses has no connection with electrical conductivity. The slag containing CaF2, Al2O3, and FeO gives the optimum Cr and Ni losses.
Keywords: High quality steel; scrap; ESR; ESR slag; electrical conductivity; Materials Science; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing